BlackGirl Geography: A (Re)Mapping Guide towards Harriet Tubman and Beyond. Issue 3 (1st December 2019) - Cahill, Loren S.
Abstract : Blackgirls have a long subaltern legacy of being geographers. We have complicated the settler-colonial project of cartography uniquely through our radical placemaking efforts towards achieving safety, inclusion, and liberation. In this autoethnographic article, I trace my own socio-spatial-sensory reflections that I experienced during my visit to Harriet Tubman's Homeplace, Senior Home, and Grave Site in Auburn, New York. I attempt to unsettle the undertheorized renderings of Tubman by interrogating her personal freedom dreams, liberation geography, and womanist cartography. I then map the intergenerational solidarity that Blackgirls have forged with Tubman more contemporarily through their own space making. I conclude by unpacking what ontological lessons both knowledge producers and organizers can glean from Tubman's geographic sacredness and savvy.